A “proto” type galectin expressed in striped bass (Morone saxatilis) tissues is released to epidermal mucus and binds to bacterial and mucus glycans - Henrikson, Davin E.; Ahmed, Hafiz; Tasumi, Satoshi; Gokara, Mahesh; Feng, Chiguang; Abernathy, Kelsey; Iqbal, Muddassar; Bianchet, Mario A.; Vasta, Gerardo R. (Frontiers in Cellular and Infection Microbiology, 2025)
Like all aquatic vertebrates and invertebrates, teleost fish are subject to the constant pressure of bacterial, fungal, and parasitic organisms present in the environmental interface that can potentially cause disease. Numerous defense molecules, including galectins, have been isolated from the skin and gut tissues of several marine and freshwater fish species. To provide new insights into the potential role(s) of galectins in the teleost fish innate immune system, we carried out studies on the striped bass (Morone saxatilis), a keystone fish species in Chesapeake Bay. We purified from epidermal skin mucus, and skin and muscle tissue, a 15-kDa galectin that we designated Msgal1-L1 (M. saxatilis galectin1-like protein 1). Both the transcript sequence and gene organization of Msgal1-L1 suggested a close relationship to the zebrafish galectin Drgal1-L2 and other proto type galectins from vertebrates, including the mammalian galectin-1. Glycan microarray analysis of Msgal1-L1 revealed a binding preference for Galβ1,4GlcNAc, and a homology structural model identified the amino acids involved in ligand recognition, both observations consistent with proto type galectins. Immunohistological examination localized Msgal1-L1 to epithelial and macrophage-/fibroblast-like cells in mucosal tissues, including skin and gill. The preliminary localization of Msgal1-L1 in free macrophage-like cells in epidermal mucus was corroborated by immunofluorescence analysis of macrophages isolated from head kidney. Msgal1-L1 binds in a carbohydrate-specific manner to O-glycosylated components of epidermal mucus. Msgal1-L1 agglutinated environmental bacterial species and strains, some of which are recognized fish pathogens, such as Vibrio and Edwardsiella spp. A microbial microarray analysis revealed that it preferentially binds to bacterial exopolysaccharides (e.g., Streptococcus and Shigella spp.) as well as various lipopolysaccharide O-antigen serotypes of Proteus spp. A preliminary solid-phase assay showed that Msgal1-L1 strongly bound Streptococcus sp., but very weakly to Mycobacterium marinum, an endemic pathogen of striped bass in Chesapeake Bay. Taken together, this evidence suggests that Msgal1-L1 may function in defense recognition against environmental bacteria by agglutinating and/or cross-linking them to mucus oligosaccharides to immobilize them within the epidermal mucus film and prevent their access to the fish epithelial cell surface. M. marinum would evade this defense mechanism to reach and infect the fish skin epithelial layer.